2018
DOI: 10.1115/1.4041494
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Optimization, Characterization, and Experimental Investigation of Additively Manufactured Communicating Microchannels

Abstract: The degree of complexity in internal cooling designs is tied to the capabilities of the manufacturing process. Additive manufacturing (AM) grants designers increased freedom while offering adequate reproducibility of microsized, unconventional features that can be used to cool the skin of gas turbine components. One such desirable feature can be sourced from nature; a common characteristic of natural transport systems is a network of communicating channels. In an effort to create an engineered design that util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…PBF technologies permit superior flexibility to fabricate complex functional channels for thermal management systems [7,16], including mini-and micro-channels [17][18][19]. Many researchers have employed this capacity to create cooling channels with enhanced thermal performance features such as waviness [20], interconnectivity [21], permeability [22], internal pin fins [23], and longitudinal vortex generators [24].…”
Section: Nomenclaturementioning
confidence: 99%
“…PBF technologies permit superior flexibility to fabricate complex functional channels for thermal management systems [7,16], including mini-and micro-channels [17][18][19]. Many researchers have employed this capacity to create cooling channels with enhanced thermal performance features such as waviness [20], interconnectivity [21], permeability [22], internal pin fins [23], and longitudinal vortex generators [24].…”
Section: Nomenclaturementioning
confidence: 99%
“…Kirsch et al [44] used AM to make micro-scale design optimizations for efficient heat removal. At the micro-scale, the surface finish plays a significant role in the heat transfer and pressure loss of any cooling design They observed that additively manufactured cooling channels have shown the surface roughness increases both heat transfer and pressure loss to similar levels as highly engineered turbine cooling schemes.…”
Section: Am For Gas Steam and Combined Cycle Applicationsmentioning
confidence: 99%